Comparative study of different methodologies for synthesis of nanogels as potential drug carriers - Balogh, Tatiana Santana (2023)
Nanogels are defined as nanometer-scale polymeric gels, considered innovative and promising nanomaterials for drug delivery systems. This joint Polish-Brazilian work aimed to contribute to the development of the area of production of nanogels by means of ionizing radiation, investigating different synthesis methodologies, namely gamma and electron beam-induced irradiation. Original and innovative method of nanogel synthesis via ultraviolet-induced radiation has been proposed in an unprecedented manner and successfully developed. Additionally, the possibility of conjugation of selected nanogels with technetium-99m (99mTc) has been investigated as a possible theranostic agent. In case of ionizing radiation-supported techniques influence of solution concentration, type of gas saturation and dose on physicochemical properties of irradiation products have been analysed. In the UV methodology different ratios of the number of OH radicals available in the system per number of monomeric units were evaluated with and without argon saturation. All samples were characterized in relation to weight-average molecular weight (Mw), Z-average radius of gyration (Rg), hydrodynamic radius (Rh) and second virial coefficient using DLS and SLS techniques. The ratio of the radius of gyration to the hydrodynamic radius (Rg/Rh), the polymer coil density (ρcoil), morphology by SEM and TEM, and topography by AFM were determined. Radiolabelling with technetium-99m was carried out both via direct and indirect methodology, in addition to purification and radiochemical stability tests. PVP K-90-based nanogels of different crosslink densities were successfully obtained in all proposed methods. It has been found that the use of nitrous oxide promoted higher number of hydroxyl radicals, favouring the formation of intramolecular crosslinking. The increase in the amount of OH radicals available in the medium (both by increase of the ionizing radiation dose and concentration of OH radical precursor (H2O2)) provided higher influence of intramolecular crosslinking. It was possible to radiolabel and purify PVP K-90 nanogels produced by e-beam and gamma irradiation with technetium-99m through [99mTc(CO)3(H2O)3]+.